Effect of climate variability and climate change on crop production and water resources in Cyprus - Bruggeman, Adriana; Zoumides, Christos; Pashiardis, Stelios; Hadjinicolaou, Panos; Lange, Manfred A.; Zachariadis, Theodoros (My University, 2011)
Crop production in Cyprus is constrained by a highly variable climate, limited precipitation and high temperatures. In addition, global climate change and water management policies that support the sustainable use of water resources are also reducing irrigation water supply. The main aims of this study were (i) to assess trends in climate parameters during the past 30 years; (ii) to assess the effect of climate variability on changes in agricultural land use, production and irrigation water demand; and (iii) to assess the effect of possible climate change scenarios and reduced irrigation water supply on crop production for the last seven seasons of this decade (2013/14-2019/20). A daily soil water balance model, based on the FAO dual crop coefficient approach, referred to as the Green-Blue Water Model, was developed to compute the crop soil water use, originating from precipitation (green water) and from irrigation (blue water). Crop area and production data for 30 seasons (1979/80-2008/09), 87 different crops and 431 communities were obtained from the Agricultural Statistics and Censuses. Crop areas registered by the Cyprus Agricultural Payment Organisation (CAPO) in 2010 were used to simulate future scenarios. Daily climate data from 34 stations and precipitation data from 70 gauges were used for the water balance computations. The monthly averages of the daily minimum temperatures were found to have statistically significant upward trends, at the 5% significance level, for the summer months at all four stations that were analyzed for trends (Larnaca, Kornos, Platania and Prodromos). The monthly averages of the daily maximum temperatures were also found to have statistically significant positive trends at Prodromos in the Troodos mountains (five months), Kornos in the eastern foot hills of the mountains (seven months), and Larnaca at the coast (nine months). Precipitation was highly variable and the only statistically significant trend was a downward trend for March at Kornos. The total harvested area of temporary (annual) crops peaked at 101.9×103 ha in 2005, after a sequence of three wet seasons, and dwindled to 70.9×103 ha during the 2008 drought year. The harvested permanent crop area decreased by nearly 40%, from 62.2×103 ha in 1980 to 38.4×103 ha in 2009. The main loss was for the vine growing area, which decreased from 34.3 to 8.3×103 ha, and for the areas planted with nut trees, which shrank from 13.3 to 5.3×103 ha, while the olive area increased from 5.7 to 12.0×103 ha. The 1980/81-2008/09 seasons were divided in seven dry years, fifteen average and seven wet years, based on their aridity ratio (precipitation over reference evapotranspiration). Average annual crop production was 8% lower during the dry years and 5% higher during the wet years, relative to the production during the fifteen average years. Model computations indicated that total blue water use averaged 190×106 m 3 /yr during the 1980/81-2008/09 seasons and was only 2% higher during the dry years and 2% lower during the wet years. Blue water was computed to have peaked at 219×106 m3 in 1989/90, while it fell to a record low (150×106 m3 ) during the 2007/08 drought year. Total green water use ranged between 135×106 m3 in 2007/08 and 368×106 m3 in 2003/04. The irrigated areas occupied 23% of the cropland, but were responsible for 65% of the total national crop production, while consuming 48% of the blue and green water used by crops. The rain-fed areas produced on average 273×103 ton/yr, fueled by 277×106 m3 /yr green water. This water may otherwise have returned back to the atmosphere without much local benefit. Climate change projections for Cyprus from an ensemble of six Regional Climate Models, under the medium A1B emission scenario of the UN Intergovernmental Panel on Climate Change (IPCC-SRES), indicated an increase in temperatures and highly variable but slightly lower precipitation amounts for the 2013/14-2019/20 seasons. Two climate scenarios were simulated: (1) a worst case scenario, represented by the seven dry years from the 1980/81-2008/09 record; and (2) a medium scenario made up of three dry years, two average years and two wet years, each with the highest evapotranspiration rates within their class. For both scenarios, irrigation water demand was reduced to 129×106 m3 /yr, as recommended by recent national water management policies, which was achieved by reducing all irrigated crop areas of the 2010 CAPO crop areas by 25%. The computed annual national crop production for 2013/14-2019/2020 was reduced by 41%, on average, under scenario 1 and by 43% under scenario 2, relative to 1980/81-2008/09. The average loss of irrigated production was 193×103 ton/yr under scenario 1 and 216×103 ton/yr under scenario 2, whereas the average rain-fed production loss was 132×103 ton/yr (scenario 1) and 125×103 ton/yr (scenario 2). These results indicated that within the near future water management policies could be critical for agriculture. Of course, irrigation water supply is likely to be reduced even further by climate change. The modeling analysis also showed high variability in water use for the different crops, communities and years, indicating that there are various options for climate change adaptation.
Keywords: Climate Variability Effects; Climate Change; Crop Production; Water Resources